How do you solve this for y?

1 – 2\3 y = 9\5 – y\5 + 3\5

1 – 2\3 y = 9\5 – y\5 + 3\5

1 - 2/3y = 9/5 - y/5 + 3/5

15(1 - 2/3y = 9/5 - y/5 + 3/5) {multiplied entire equation by common denominator, 15}

15(1) - 15(2/3y) = 15(9/5) - 15(y/5) + 15(3/5) {multiplied each term by 15}

15 - 10y = 27 - 3y + 9 {cancelled and multiplied}

15 - 10y = 36 - 3y {combined like terms}

15 = 36 + 7y {added 10y to both sides}

-21 = 7y {subtracted 36 from both sides}

y = - 3 {divided both sides by 7}

- Algebra House